2021
DOI: 10.3897/oneeco.6.e65582
|View full text |Cite
|
Sign up to set email alerts
|

Applying the System of Environmental Economic Accounting-Ecosystem Accounting (SEEA-EA) framework at catchment scale to develop ecosystem extent and condition accounts

Abstract: Ecosystem accounting is a tool to integrate nature into decision-making in a more structured way. Applying the use of nationally available datasets at catchment scale and following the System of Environmental Economic Accounting-Ecosystem Accounting (SEEA-EA) framework, we present results from a catchment case study in Ireland, highlighting findings specifically in relation to the development of ecosystem extent and condition accounts. In the absence of a national ecosystem map, CORINE landcover mapping formed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…The SEEA EA was adopted as a statistical standard in 2021 and comprises a geospatial approach, whereby existing data on ecosystem stocks and flows are collated to show changes over time (Obst 2015, Eigenraam and Obst 2018, UNSD 2021. Designed since inception to align with the System of National Accounts (SNA), the SEEA EA can be applied at national scale (Eigenraam and Obst 2018), but can equally be used at smaller spatial scales (Farrell et al 2021b). Developed in the EU context through the MAES, MAIA and INCA projects, the SEEA EA has been identified as a key tool to deliver on the EU Strategy for Biodiversity 2030, particularly in relation to monitoring outcomes of the EU nature restoration plan where legally binding targets will be set for each EU Member State, requiring a scientific basis to establish realisable restoration targets (Vysna 2021).…”
Section: Ecosystem Accounting To Support Restorationmentioning
confidence: 99%
See 2 more Smart Citations
“…The SEEA EA was adopted as a statistical standard in 2021 and comprises a geospatial approach, whereby existing data on ecosystem stocks and flows are collated to show changes over time (Obst 2015, Eigenraam and Obst 2018, UNSD 2021. Designed since inception to align with the System of National Accounts (SNA), the SEEA EA can be applied at national scale (Eigenraam and Obst 2018), but can equally be used at smaller spatial scales (Farrell et al 2021b). Developed in the EU context through the MAES, MAIA and INCA projects, the SEEA EA has been identified as a key tool to deliver on the EU Strategy for Biodiversity 2030, particularly in relation to monitoring outcomes of the EU nature restoration plan where legally binding targets will be set for each EU Member State, requiring a scientific basis to establish realisable restoration targets (Vysna 2021).…”
Section: Ecosystem Accounting To Support Restorationmentioning
confidence: 99%
“…Supplementary datasets provided more detail on the extent of specific peatland types (Article 17 datasets and industrial peat extraction data). We used peat soil texture datasets, developed at national level, as an indicator of the former extent of peatland in each catchment (pre-2000) as demonstrated in Farrell et al (2021b).…”
Section: Building Seea Ea Accountsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the United Nations Statistical Commission adopted in March 2021 the SEEA Ecosystem Accounting framework. This framework was tested by Farrell et al (2021), who found it to be both feasible and effective for the management of water resources. It provides a clear path between ecosystem characteristics (ecosystem extent and conditions), monetary ecosystem assets, and human well-being.…”
Section: What Next?mentioning
confidence: 99%
“…The leading international framework for developing environmental economic accounts is the System of Environmental Economic Accounting -Ecosystem Accounting (SEEA-EA) which has been adopted by the UN Statistical Commission and many countries (United Nations 2021). While ecosystem extent indicators have been widely studied, there has been limited testing of how effectively condition indicators in SEEA-EA (Farrell et al 2021), and biodiversity indicators more generally (Watermeyer et al 2021;Nicholson 2020), can inform management decisions.…”
Section: Introductionmentioning
confidence: 99%